A Risk of Venous Thromboembolism Algorithm as a Predictor of Venous Thromboembolism in Patients with Colorectal Cancer - Ying Chen MB; Yanchun Wang MD; Suhong Xie MM; Hui Zheng MD; Ying Tong MM; Xiang Gao MM; Renquan Lu MD; Lin Guo MD (Clinical and Applied Thrombosis/Hemostasis, 2021)
Cancer patients experience an increased risk of venous thromboembolism (VTE). In this study, we investigated a risk of venous thromboembolism algorithm (RVTA) in patients with colorectal cancer and evaluated its ability to predict the prognosis of colorectal cancer. We retrospectively analyzed clinical data from 345 patients with colorectal cancer from January 2015 to December 2018 at the Shanghai Cancer Center to develop the RVTA. Additionally, the 345 patients were followed until December 2020 for prognostic analysis. The RVTA included the following variables: (a) platelet count, (b) blood transfusion history, (c) metastasis, (d) multiple chemotherapy regimens, and (e) the D-dimer level. Good predictive efficiency was observed for the RVTA (AUC was 0.825; 95% CI was 0.721 to 0.930). The median progression-free survival (PFS) of patients who had a score less than 4 (0-3), defined as the low-risk group, was significantly longer than that of the high-risk group, which included patients who had a score greater than 4 (4-8) (26 vs ten months, P  < .001). The RVTA was a valuable predictor for VTE risk and had prognostic value in colorectal cancer.